Sedimentation changes in the Breede River estuary: A study of sedimentation changes on the flood tide delta in the estuary, with reference to the hydrology of the river - De Villiers, Louis (Department of Environmental and Geographical Science, 2016)
The study examines sedimentation changes on the flood tide delta in the Breede River estuary since 1942, and relates these changes in sedimentation to changes in the hydrology of the river, as a consequence of damming the river and its tributaries. Sequential aerial photography is used to determine changes in the extent of the Zostera beds on the flood delta, this being indicative of changes in the substrate sediments. Four cores were taken from the flood delta, and standard grainsize analysis techniques employed to establish the composition and characteristics of the sediments. Together with survey work and other ancillary information, these twci techniques enable description of the sedimentation changes and the present sediment dynamics on the flood tide delta. Virgin catchment runoff was simulated using two models, having rainfall data as the primary input. Simulated and actual runoff, as determined from gauge plate data, were qualitatively compared in terms of mean monthly runoff and cumulative annual runoff. This, together with an examination of temporal increases in the total volume of water impounded in the catchment, enables the impact of dams on the hydrology of the river to be determined. It is found that there has been a virtually complete annihilation of the mudflat the Zostera beds, a concomitant loss of the areas, and that the sediments presently occurring on the flood delta are almost wholly of marine origin. Temporally, these changes correlate well with increased impoundment of runoff in the catchment. It is concluded that there has been an increase in marine sedimentation on the flood tide delta, and that this change in sedimentation is directly related to and consequent upon changes in the hydrology of the river as a result of impounding catchment runoff.